CEREBROVASCULAR DISORDERS: ISCHEMIC STROKE IS CAUSED BY CERDIOEMBOLIC SOURCE AND ATRIAL FIBRILLATION (Scientific Conference on Multidisciplinary Studies, 2025)
Ischemic stroke is the fifth leading cause of death and a major condition feared by older adults. Clinical identification of patients with cerebral ischemia is important to provide appropriate, immediate treatment and initiate stroke preventive strategies. Ischemic stroke is also called brain ischemia and cerebral ischemia. Ischemia is the medical term for “lack of blood supply.” The blockage is often caused by blood clots or fatty deposits inside the blood vessel. According to the American Stroke Association, ischemic is the most common type of stroke, accounting for about 87% of all stroke cases.